Does Greater Exchange Rate Flexibility Affect Interest Rates in Post-Crisis Asia? - Chow, Hwee Kwan (Institutional Knowledge at Singapore Management University, 2006)
In post-crisis Asia, all crisis-hit countries (except Malaysia) announced a shift from an exchange rate based monetary policy framework to the adoption of inflation targeting which uses interest rates as the monetary policy operating instrument. In this study, we examine the empirical relationship between exchange rates and interest rates by applying a bivariate VAR-GARCH model to the Asian crisis countries, namely Indonesia, Korea, Philippines and Thailand. The findings suggest that, following the crisis, their currencies exhibit greater sensitivity to competitors' exchange rates, and that increased exchange rate flexibility stabilizes interest rates only in the short run.